Shape transition and collective excitations in neutron–rich 170-178Yb Nuclei - Sharrad, Fadhil; Okhunov, Abdurahim (Publishing House of the Romanian Academy, 2012)
Energy levels, B(E2) values and potential energy surface for even-even 170-178Yb isotopes have been calculated using the IBM-1. The predicted energy levels, B(E2) values and intrinsic quadrupole moments Q0 results were reasonably consistent with the experimental data. The contour plot of the potential energy surfaces shows all interest nuclei were deformed and have rotational characters.